Achieving Environmental and Fiscal Goals in Lithuania using Environmental Taxes - Čiegis, Remigijus; Jankauskas, Vidmantas; Štreimikienė, Dalia (Ekonomika, 2002)
The main aim of this article is to analyse and compare the former and revised system of environmental taxes in Lithuania. Conceptual, analytical and methodological issues associated with the use of these instruments in the Lithuanian context are thoroughly discussed. Comparative and system analysis allows revealing deficiencies of the previous system of taxes and positive features of the new system. Comparison of pollution taxes available in Lithuania with the damage costs related to these pollutants emissions as well as comparison of environmental taxes with those of EU and accession countries allows to evaluate the efficiency of existing tax system in Lithuania and provide recommendations for strategic actions with respect of increasing effectiveness of existing environmental taxation system.